Изотопный состав кислорода воды рудообразующего флюида в зоне амфиболовых метасоматитов Сергеевского месторождения золота (Украинский щит) - Фомин, Ю.А.; Демихов, Ю.Н. (Видавничий дім "Академперіодика" НАН України, 2007)
The oxygen isotope composition of the ore forming fluid water in gold-bearing amphibole metasomatites has been investigated: δ18O H2O are +5.6...–7.1‰ in the temperature diapason of 350–130 °C. The mineralogical(dolomite-calcite) and isotopic (δ18O of quartz, carbonates, and water) zoning was found. The genetic connection of ores with the geochemical barrier under conditions of the lime and magnesium contact-metasomatic process is assumed.